Taksonomi Tujuan Pendidikan dan Evaluasi Hasil Belajar - Mauridhatul Kasanah; Arga Putra Pratama (CV Edu Tech Jaya, 2024)
This research examines the taxonomy of educational objectives through a library research approach, referring to seminal works such as